Development of prototype of wireless footwork analysis for badminton player - Al Nakheel Narin, Alwakil (2021)
This research examines the agility training in badminton is very important. Our group design a device and program that can help badminton player train to be more agile. We will use electronic part to create a device and coding to develop a system that can monitor the performance of the player. The result can be shown after training so player can be improving later. There is graph and data so player can analyses it.